Method development and validation for the determination of Metformin HCL and Empagliflozin in its bulk and pharmaceutical dosage forms by RP-ultra performance chomatography method - B. SURENDRA BABU; K.S.NATARAJ; A.K.M. PAWAR; K. GNANANATH (International Journal of Pharma and Bio Sciences, 2017)
A simple, rapid and sensitive analytical procedure was developed for the simultaneous estimation of Metformin and Empagliflozin by RP-UPLC method in bulk drug and pharmaceutical dosage form. The quantification was carried out isocratically using BEH C18 column (2.5×50mm) 3µ with a flow rate 0.3 ml/min. The mobile phase comprises of 70:30 v/v Acetonitrile: phosphate buffer pH: 3. the eluents were detected by UV detector at 220 nm. The retention times for Metformin and Empagliflozin were found to be 0.879 mins and 1.294 mins respectively. The method was validated as per ICH guidelines for linearity, accuracy, precision and robustness. The developed method shows good linearity over the concentration range of 50µg/ml-150µg/ml and 5µg/ml-25µg/ml with the average percentage recoveries were in the range of 99.56% and 99.48% for Metformin and Empagliflozin respectively. The limits of detection (LOD) value were 0.12 and 0.015 ppm and whereas limits of quantification (LOQ) value was 0.42 and 0.05 ppm for Metformin and Empagliflozin respectively. Therefore, the proposed method can be applied for routine analysis of the bulk drugs as well as combined pharmaceutical dosage forms of Metformin and Empagliflozin.